Residents' use of mobile technologies: three challenges for graduate medical education. (10th April 2017) - MacLeod, Anna; Fournier, Cathy
Abstract : Introduction: The practice of medicine involves, among other things, managing ambiguity, interpreting context and making decisions in the face of uncertainty. These uncertainties, amplified for learners, can be negotiated in a variety of ways; however, the promise, efficiency and availability of mobile technologies and clinical decision supports make these tools an appealing way to manage ambiguity. Mobile technologies are becoming increasingly prevalent in medical education and in the practice of medicine. Because of this, we explored how the use of mobile technologies is influencing residents' experiences of graduate medical education. Methods: We conducted an 18-month qualitative investigation to explore this issue. Our research was conceptually and theoretically framed in sociomaterial studies of professional learning. Specifically, our methods included logging of technology use and related reflexive writing by residents (n=10), interviews with residents (n=12) and interviews with faculty (n=6). Results: We identified three challenges for graduate medical education related to mobile technology use: (1) efficiency versus critical thinking; (2) patient context versus evidence-based medicine and (3) home/work-life balance. Discussion: In this digital age, decontextualised knowledge is readily available. Our data indicate that rather than access to accurate knowledge, the more pressing challenge for medical educators is managing how, when and why learners choose to access that information.